Finite approximation of descending HNN-expansions of groups - Moldavansky, D. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The paper examines the special case of the general construction of HNN-extensions of groups in which at least one of the associated subgroups is the base group. A criterion is determined for a group obtained in this way to be residually finite. Any group obtained as such an extension from a free nilpotent group of finite rank is residually finite.